1999
DOI: 10.1007/bf02783905
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro effects of zinc on markers of bone formation

Abstract: Zinc deficiency is associated with a reduced rate of bone formation that can be corrected by supplementation of the deficient diet with adequate amounts of zinc. This study was conducted to examine the effects of zinc on bone cell parameters associated with bone formation. Tibiae were removed from 19-d-old chicken embryos and incubated for 48 h in Dulbecco's modified Eagle's medium supplemented with antibiotics, bovine serum albumin, and HEPES. The addition of zinc (25-200 g/dL) to tibial cultures resulted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 18 publications
1
24
1
Order By: Relevance
“…Anderson et al [27] concluded that the early phase of mineralization was closely associated with tissue non-specific alkaline phosphatase. According to a previous report [28], addition of Zn to bone culture resulted in a concentrationdependent increase in alkaline phosphatase activity. Although we did not evaluate the alkaline phosphatase activity in our study, we hypothesize that the differences in mineralization of osteoblasts with Zn exposure during the early phase may partly be due to cellular alkaline phosphatase activity.…”
Section: Discussionmentioning
confidence: 84%
“…Anderson et al [27] concluded that the early phase of mineralization was closely associated with tissue non-specific alkaline phosphatase. According to a previous report [28], addition of Zn to bone culture resulted in a concentrationdependent increase in alkaline phosphatase activity. Although we did not evaluate the alkaline phosphatase activity in our study, we hypothesize that the differences in mineralization of osteoblasts with Zn exposure during the early phase may partly be due to cellular alkaline phosphatase activity.…”
Section: Discussionmentioning
confidence: 84%
“…Recent reported studies of osteoblast intermediary energy metabolism [such as 2530] have not included any involvement of the specialized metabolic relationships of citrate and/or zinc in osteoblasts. Chen et al in their 1999 report of zinc effects on bone formation [31] emphasized that “ Studies of bone in tissue culture typically do not include addition of zinc specifically… Interpretation of data from such studies should take this variable (zinc) into account. ” The important relationship of zinc accumulation on cellular citrate metabolism as described above (Fig.…”
Section: Are Osteoblasts the Specialized “Citrate-producing” Cells Inmentioning
confidence: 99%
“…Zn inhibits osteoclast differentiation and promotes osteoblast activity and promotes bone formation [15,16], and it is also an important trace element found in bone. Zn is also involved increasing biomineralization both in vivo and in vitro [17,18].…”
Section: Introductionmentioning
confidence: 99%